Lack of activity of betulin‐based Oleogel‐S10 in the treatment of actinic keratoses: a randomized, multicentre, placebo‐controlled double‐blind phase II trial. (25th February 2015) - Pflugfelder, A.; Andonov, E.; Weide, B.; Dirschka, T.; Schempp, C.; Stockfleth, E.; Stratigos, A.; Krüger‐Krasagakis, S.; Bauer, J.; Garbe, C.; Eigentler, T.K.
Summary Background Betulinic acid and other triterpenes have shown strong antitumour activity in vitro and in vivo. A triterpene extract of birch bark formed the base of Oleogel‐S10 and allowed topical application. Two previous trials have shown efficacy and tolerability in the treatment of actinic keratoses (AKs) with betulin‐based Oleogel‐S10. Objectives To confirm the efficacy and tolerability/safety of Oleogel‐S10 in the treatment of AKs in a multicentre placebo‐controlled study. Methods Patients (n = 165) were treated topically for 3 months in a four‐arm parallel study design, randomly allocated to A (n = 53) Oleogel‐S10 once daily, B (n = 51) Oleogel‐S10 twice daily, or C (n = 25) or D (n = 28) placebo (petroleum jelly) once or twice daily, respectively. Clinical efficacy in this double‐blind study was assessed by the investigators. Final and baseline biopsies were evaluated by central histopathology. Results Complete clearance of the target lesions was seen in 4% of patients in group A and 7% in group B, but not in the placebo groups. A clearance rate of > 75% was seen for 15% and 18% of patients in groups A and B, respectively, and for 13% in the placebo groups. These differences were not statistically significant. Histopathologically, 43·9% of patients showed a downgrading or clearance of the marker AK with no significant differences between the groups. Treatment with Oleogel‐S10 was well tolerated. The tolerability as assessed by the investigator was mostly 'very good' (78·8%), followed by 'good' (18·2%) and only 1·2% assessed it as 'intolerable'. Patient‐assessed tolerability was graded mostly 'very good' (56·4%) or 'good' (34·5%). Conclusions Treatment with Oleogel‐S10 was well tolerated during a treatment period of 3 months, yet was no better than placebo in terms of efficacy in the treatment of AKs.